To be or not to be – that is the question: Fraudulent practices in scientific publishing - Zubchenko, Nadiia; Зубченко, Надія Ігорівна; Зубченко, Надежда Игоревна (My University, 2019)
The realities of the scientific world prove that the status of a scientist is an image that has several components. Not the last role in it plays the academic integrity. But is it worth to speak about academic integrity, when a modern scholar at each step encounters such phenomena as violation of copyright, as "predatory publishers", as fake scientific journals? Non-integrity has many manifestations and variations, besides, this is not only a person’s of a scientist characteristic, but also some other subjects’ of the scientific process. Turning to the issue of copyright and integrity, we should mention publishers. "Predatory publishers", "Beall's list" - everyone has heard about it, someone have faced. The algorithms of the activity of these publishing houses are very similar to fraudulent manipulations: “predator” in every way trying to lure as many researchers as possible and obtain the maximum benefit (material in particular). "Predators" often operate in two ways: - copyright infringement (publication in "non-impactful" or unofficial publications, including scholars in editorial boards without their permission, reprints of publications without the permission of authors and other publishers, etc.); - fraudulent practice (reprint of publications without the consent of the right holder, the use of titles of known editions, their ISSN, substitution of the impact factor, source data of the publication for misleading, manipulations with personal data). Apparently, the Hamlet question "to be or not to be" can be moved to modern science, since each researcher sooner or later ponders over the dilemma of integrity: to publish an article as soon as possible, anywhere, or to weigh all the pros and contras and make a high-quality publication? Academic integrity and publishers' integrity: how to be honest and famous in science?
Zubchenko N. To be or not to be – that is the question: Fraudulent practices in scientific publishing : workshop [Електронний ресурс] // Digitale Horizonte Innovation für Gedächtnis- und Forschungsinstitutionen (Graz, Österreich, 28 Febr. 2019 - 1 März 2019). - Режим доступу: http://conference.ait.co.at/digbib/index.php/digbib2019/digbib2019/paper/view/162 ; http://dspace.onua.edu.ua/handle/11300/12233 DOI: 10.13140/RG.2.2.25943.70565
Keywords: конференція; публікаційна активність; шахрайські практики; академічна доброчесність; conference; publication activity; fraudulent practices; academic integrity; academic publishing; конференция; публикационная активность; мошеннические практики; академическая добропорядочность